CODE-SWITCHING AND CODE-MIXING IN THE LANGUAGE USE OF INFLUENCER @LINGLINGLIEANTI ON TIKTOK - Amiroh, Putri Dinah; Ulfiyani, Siti; Mukhlis, Mukhlis; Riwayati Utami, Hadi (JURNAL KONFIKS, 2025)
The phenomenon of code-switching and code-mixing has become increasingly prominent in digital communication, particularly on social media platforms. TikTok, as a multimodal medium, provides a unique space for the blending of local and global linguistic resources. This study aims to describe the types of code-switching and forms of code-mixing employed in the TikTok content of @linglinglieanti, as well as to identify the underlying social and pragmatic factors. Adopting a descriptive qualitative approach, the study analyzed 34 videos uploaded in January 2025. Data were collected through free listening observation, documentation, and note-taking techniques, and analyzed using a combination of the matching method and distribution method. The findings reveal that external code-switching (Indonesian–English, Javanese–English, Indonesian–Korean, and Mandarin–Indonesian) is more dominant than internal switching (Indonesian–Javanese). Code-mixing occurred in the forms of words, reduplications, word groups, and clauses. The factors driving these phenomena include global cultural trends, cultural identity, humor and stylistic strategies, the prestige of foreign languages, interpersonal intimacy, and lexical gaps. These results demonstrate that code-switching and code-mixing in digital contexts are not random occurrences but adaptive strategies functioning as communicative tools, identity markers, and performative acts. Theoretically, this study contributes to sociolinguistic inquiry in digital contexts, while practically, it offers insights for language learning, digital literacy, and multilingual awareness.